Genetic and Phenotypic Characterization of the Novel Metallo-β-Lactamase NDM-29 From Escherichia coli - Zhu, Ying; Jia, Xinmiao; Jia, Peiyao; Li, Xue; Yang, Qiwen (Frontiers in Microbiology, 2021)
Objectives: The NDM can hydrolyze almost all clinically-available β-lactam antibiotics and has widely spread all over the world. NDM-29, a novel carbapenemase, was discovered in an Escherichia coli (19NC225) isolated from a patient with biliary tract infection in 2019 in China. Methods: Conjugation, transformation, cloning test, fitness cost, PacBio Sequel and Illumina sequencing were performed to analyze the genetic and phenotypic characterization of blaNDM-29. Results: The susceptibility testing results showed 19NC225 was resistant to cephalosporins, carbapenems, combinations of β-lactam and β-lactamase inhibitors and levofloxacin. Conjugation and transformation were performed to verify the transferability of NDM-29-encoding plasmid and cloning test was conducted to prove the function of blaNDM-29 to increase carbapenem-resistance. Furthermore, fitness cost test confirmed that the presence of NDM-29 exerts no survival pressure on bacteria. PacBio Sequel and Illumina sequencing were performed to analyze the genetic characterization of 19NC225, which contains two plasmids (pNC225-TEM1B, pNC225-NDM-29). pNC225-NDM-29, exhibiting 99.96% identity and 100% coverage with pNDM-BTR (a IncN1 plasmid from an E. coli in urine specimen from Beijing in 2013), showed responsibility for the MDR phenotype. Compared with blaNDM-1, blaNDM-29, located on pNC225-NDM-29, carries a G388A (D130N) mutation. The region harboring blaNDM-29 is located in a ISKpn19-based transposon and two Tn6292 remnants are symmetrically located upstream and downstream of the transposon. The sequence results also indicated several important virulence genes. Conclusion: The findings of the novel carbapenamase NDM-29 could pose a threat to the control of antimicrobial resistance and arouse attention about the mutation of bacteria.